New approaches to stability analysis for time-varying delay systems. Issue 7 (May 2019) - Zhang, Ruimei; Zeng, Deqiang; Park, Ju H.; Zhong, Shouming; Liu, Yajuan; Zhou, Xia
Abstract: In this paper, two new estimation approaches namely delay-dependent-matrix-based (DDMB) reciprocally convex inequality approach and DDMB estimation approach, are introduced for stability analysis of time-varying delay systems. Different from existing estimation techniques with constant matrices, the estimation approaches are with delay-dependent matrices, which can employ more free matrices and utilize more information of both time delay and its derivative. Based on the estimation approaches, less conservative stability criteria with lower computational complexity are derived in the form of linear matrix inequalities (LMIs). Finally, two numerical examples are given to illustrate the advantages of the proposed methods.